2019
DOI: 10.1021/acs.jmedchem.9b00911
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic Boronate VNRX-5133 Inhibits Metallo- and Serine-β-Lactamases

Abstract: The bicyclic boronate VNRX-5133 (taniborbactam) is a new type of β-lactamase inhibitor in clinical development. We report that VNRX-5133 inhibits serine-β-lactamases (SBLs) and some clinically important metallo-β-lactamases (MBLs), including NDM-1 and VIM-1/2. VNRX-5133 activity against IMP-1 and tested B2/B3 MBLs was lower/not observed. Crystallography reveals how VNRX-5133 binds to the class D SBL OXA-10 and MBL NDM-1. The crystallographic results highlight the ability of bicyclic boronates to inhibit SBLs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(185 citation statements)
references
References 56 publications
9
176
0
Order By: Relevance
“…Indeed, many research groups have developed MBL inhibitors and confirmed their activity against purified MBL enzymes in vitro; however, most inhibitors showed extremely low activity toward live MBL-producing bacteria, suggesting that their permeativity of the bacterial outer membrane is low (7). Thus, only a few MBL inhibitors, such as ME1071, developed by Meiji Seika Pharma (8), and cyclic boronates (9,10), including VNRX-5133 (taniborbactam), developed by Venatorx (11)(12)(13), and ANT431, developed by Antabio SAS (14), are reportedly active against MBL-producing clinical isolates. Nonetheless, none of these compounds have been approved for clinical use.…”
mentioning
confidence: 99%
“…Indeed, many research groups have developed MBL inhibitors and confirmed their activity against purified MBL enzymes in vitro; however, most inhibitors showed extremely low activity toward live MBL-producing bacteria, suggesting that their permeativity of the bacterial outer membrane is low (7). Thus, only a few MBL inhibitors, such as ME1071, developed by Meiji Seika Pharma (8), and cyclic boronates (9,10), including VNRX-5133 (taniborbactam), developed by Venatorx (11)(12)(13), and ANT431, developed by Antabio SAS (14), are reportedly active against MBL-producing clinical isolates. Nonetheless, none of these compounds have been approved for clinical use.…”
mentioning
confidence: 99%
“…The home page also includes a short feature called the "MBL Inhibitor of the Month." For the launch of the website, the developers chose to highlight recent work from Professor Chris Schofield's group at the University of Oxford (Oxford, UK) regarding his bicyclic boronate (VNRX-5133, Venatorx Pharmaceuticals, Malvern, PA, USA) inhibitor [16]. Professor Schofield and coworkers wrote a short perspective of the compound, and it is the intent to highlight new compounds each month.…”
Section: Resultsmentioning
confidence: 99%
“…However, this compound is a poor inhibitor of subclass B1 MBL NDM-1 New Delhi MBL (NDM)-1) [15]. Another example is the bicyclic boronate VNRX-5133, which exhibits good inhibition against NDM and other subclass B1 enzymes [16]; however, this compound is not a good inhibitor of subclass B3 MBL L1 [16]. Secondly, it is imperative that any clinical MBL inhibitor be selective towards bacterial MBLs over human MBL-fold containing enzymes, some of which have important physiological roles [6].…”
Section: Introductionmentioning
confidence: 99%
“…Taniborbactam is a bicyclic boronate and acts as a dual action inhibitor of both serine β lactamases (SBLs) and MBLs 47,48 . The broad inhibitory activity includes class A and class C enzymes as well as the MBLs NDM and VIM, but not IMP, and moderately the OXA48 carbapenemase (class D) 47 . In combina tion with cefepime, the MICs against NDM producing and VIM producing Enterobacterales are increased, and 10% to 20% of strains are resistant 49 .…”
Section: Wwwnaturecom/nrmicromentioning
confidence: 99%